Niat dan Perilaku Whistleblowing Auditor Pemerintah - Arif, Muhammad Faisal; Sukarno, Zulfikry (JURNAL AKUNTANSI, 2023)
ABSTRACTThis study aims to examine the Theory of Planned Behavior (TPB) construct in the whistleblowing behavior of government auditors. Respondents in this study were BPK auditors representing South Sulawesi, totaling 86 respondents. The tool used in data management uses Partial Least Square (PLS). The results showed that whistleblowing attitudes, subjective norms, and perceived behavioral control had a significant positive effect on whistleblowing intentions, the same was found in the relationship between perceived behavioral control and whistleblowing behavior. In addition, significant positive results were found in the relationship between intention and whistleblowing behavior and the relationship between subjective norms and whistleblowing attitudes. This research contributes to the BPK as a government financial auditing institution to build a work environment that can encourage their auditors to have intention and behavior as a whistleblowing. The limitation of this study lies in the scope of the population, only BPK auditors representing South Sulawesi and only conducting tests on the Theory of Planned Behavior (TPB) construct in assessing the intentions and behavior of BPK auditor whistleblowing. We hope that further research can develop by comparing the whistleblowing intentions and behavior of government external auditors (BPK) and internal auditors (BPKP and Inspectorate).